Kepositifan Induksi Sputum NaCl 3% dan Teknik Broncho Alveolar Lavage pada Pneumocystis Pneumonia: [Positivity Result of Nebulized NaCl 3% versus Bronchoalveolar Lavage in Pneumocystis Pneumonia] - Isnin Anang Marhana; Retna Dwi Puspitarini (Jurnal Respirasi, 2016)
Background: Pneumocystis pneumonia (PCP) is a major cause of morbidity and mortality in patients immunocompromised. The incidence of PCP in HIV are 0.3 cases per 100 person years with mortality 63.6%. The diagnosis of PCP experiencing difficulties because of the causative organism can not be cultured. Several attempts were carried out to obtain a representative sample sputum through induced sputum and bronchoalveolar lavage. This study compared the use of induced sputum and bronchoalveolar lavage (BAL) in the diagnosis of PCP. Methods: From September, 2015, to February, 2016, HIV-positive patients 21 to 65 years old were evaluated at UPIPI ward, Soetomo hospital with suspicion of PCP based on clinical and radiological findings. Sputum induction and BAL was done for Giemsa staining. Result: Thirteen subjects with a mean age of 40, with 11 male (84.6%). All subjects with chief complain shortness of breath and common complain cough with hard to expetorate. Most frequent risk factors was freesex. Mean of subjects received treatment cotrimoxazole is 3.5 days. Six subjects have been treated with ART. Mean of LDH serum was 554.62 ± 376.707 U/l. Interstitial infiltrate was the most frequent radiological pattern (76.9%). Most bronchoscopy examinations showed normal results (84.6%). Both Giemsa staining from induced sputum and BAL showed no positive results. Conclusion: All Giemsa staining from both induced sputum and BAL can not be compared due to no positive result.